2016
DOI: 10.1186/s12889-016-2828-0
|View full text |Cite
|
Sign up to set email alerts
|

Go!: results from a quasi-experimental obesity prevention trial with hospital employees

Abstract: BackgroundWorksite obesity prevention interventions using an ecological approach may hold promise for reducing typical weight gain. The purpose of this study was to examine the effectiveness of Go!, an innovative 12-month multi-component worksite obesity prevention intervention.MethodsA quasi-experimental non-equivalent control group design was utilized; 407 eligible hospital employees (intervention arm) and 93 eligible clinic employees (comparison arm) participated. The intervention involved pedometer distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(75 citation statements)
references
References 38 publications
0
75
0
Order By: Relevance
“…Although the majority of the studies focused their intervention on modifying both dietary and physical activity behaviors, two studies (Pohjonen & Ranta, 2001; Yuan et al, 2009) focused only on physical activity behaviors. Half ( n = 6) of the studies reported some evidence/theoretical basis for the intervention, such as Theory of Planned Behavior (LaCaille et al, 2016), Transtheoretical Model (Long & Sheehan, 2010), Cognitive-Behavioral and Social Learning Theories (LaCaille et al, 2016; Tucker et al, 2011), Behavior-Change Health Practice (Yuan et al, 2009), Ecological Framework (LaCaille et al, 2016), and Experimental Learning and Bridges’ Model of Change (Shahar et al, 2009). The majority of the studies used a combination of behavioral/educational, environmental, and organizational support strategies to modify physical activity and/or dietary behaviors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the majority of the studies focused their intervention on modifying both dietary and physical activity behaviors, two studies (Pohjonen & Ranta, 2001; Yuan et al, 2009) focused only on physical activity behaviors. Half ( n = 6) of the studies reported some evidence/theoretical basis for the intervention, such as Theory of Planned Behavior (LaCaille et al, 2016), Transtheoretical Model (Long & Sheehan, 2010), Cognitive-Behavioral and Social Learning Theories (LaCaille et al, 2016; Tucker et al, 2011), Behavior-Change Health Practice (Yuan et al, 2009), Ecological Framework (LaCaille et al, 2016), and Experimental Learning and Bridges’ Model of Change (Shahar et al, 2009). The majority of the studies used a combination of behavioral/educational, environmental, and organizational support strategies to modify physical activity and/or dietary behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…Follow-up from baseline ranged from 2 to 60 months, with only three studies (Long & Sheehan, 2010; Moy et al, 2006; Pohjonen & Ranta, 2001) reporting long-term (>12 months) weight outcomes. With regard to weight-related outcomes (Table 2), eight (73%) of the studies reported significant change in the weight outcomes favoring the intervention group as compared with the control group, whereas three (LaCaille et al, 2016; Long & Sheehan, 2010; Moy et al, 2006) reported no change in weight-related outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The TLD has been mainly used in assisting children with dietary self-monitoring to encourage the intake of lowenergy-dense foods and promote weight loss. 16,19 The TLD approach has also been widely used to assist adults with making healthier food point-of-purchase decisions, such as in cafeterias, 20,21 at concession stands, 22 and on food labels. 23 More recently, there has been an interest in using the TLD approach for self-monitoring with adults, as the TLD can be used with low-literacy populations.…”
Section: Introductionmentioning
confidence: 99%